2012
DOI: 10.1074/jbc.m111.337345
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Targets Apolipoprotein A-I, the Major High Density Lipoprotein Protein, for Site-Specific Oxidation in Human Atherosclerotic Lesions

Abstract: Background:Oxidation of apolipoprotein A-I by myeloperoxidase has been proposed to deprive HDL of its cardioprotective effects. Results: Tyrosine 192 is the major site of chlorination in apoA-I in both plasma and lesion HDL isolated from humans. Conclusion: Chlorination of apolipoprotein A-I by myeloperoxidase may contribute to generation of a dysfunctional form of HDL in vivo. Significance: Quantifying apolipoprotein A-I chlorination might help diagnose and perhaps treat human cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
178
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(190 citation statements)
references
References 71 publications
10
178
1
1
Order By: Relevance
“…Following immunoprecipitation of total apoA-I from homogenates prepared from the atherosclerotic artery wall, it was reported that NO 2 -Tyr 166 modification of apoA-I was an abundant PTM in vivo through proteomics studies (8). In contrast, in studies that followed using buoyant density centrifugation to isolate HDL-like particles, it was concluded that nitration of tyrosine at this site on apoA-I is an exceedingly low abundance product and therefore presumably of little physiologically relevance (22). The present studies unambiguously showed that nitration of apoA-I at tyrosine 166 is an exceptionally abundant modification in apoA-I in the diseased artery wall where ϳ1 of every 12 apoA-I molecules recovered harbors this PTM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following immunoprecipitation of total apoA-I from homogenates prepared from the atherosclerotic artery wall, it was reported that NO 2 -Tyr 166 modification of apoA-I was an abundant PTM in vivo through proteomics studies (8). In contrast, in studies that followed using buoyant density centrifugation to isolate HDL-like particles, it was concluded that nitration of tyrosine at this site on apoA-I is an exceedingly low abundance product and therefore presumably of little physiologically relevance (22). The present studies unambiguously showed that nitration of apoA-I at tyrosine 166 is an exceptionally abundant modification in apoA-I in the diseased artery wall where ϳ1 of every 12 apoA-I molecules recovered harbors this PTM.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics analysis of buoyant densityisolated HDL-like fractions confirms tyrosine 192 as a preferred oxidation site on apoA-I through MPO-catalyzed chlorination in both human plasma-and lesion-derived apoA-I (21,22). The major site of nitration in plasma-derived apoA-I in HDL was also reported to be tyrosine 192, whereas tyrosine 18 was found to be a major site reported from lesion "HDL-like" particlelocalized apoA-I (22).…”
mentioning
confidence: 87%
See 3 more Smart Citations